H₂O₂-Activated Mitochondrial Phospholipase iPLA₂γ Prevents Lipotoxic Oxidative Stress in Synergy with UCP2, Amplifies Signaling via G-Protein-Coupled Receptor GPR40, and Regulates Insulin Secretion in Pancreatic β-Cells - Ježek, Jan; Dlasková, Andrea; Zelenka, Jaroslav; Jabůrek, Martin; Ježek, Petr (Antioxidants & redox signaling, 2015)
AIMS: Pancreatic β-cell chronic lipotoxicity evolves from acute free fatty acid (FA)-mediated oxidative stress, unprotected by antioxidant mechanisms. Since mitochondrial uncoupling protein-2 (UCP2) plays antioxidant and insulin-regulating roles in pancreatic β-cells, we tested our hypothesis, that UCP2-mediated uncoupling attenuating mitochondrial superoxide production is initiated by FA release due to a direct H2O2-induced activation of mitochondrial phospholipase iPLA2γ. RESULTS: Pro-oxidant tert-butylhydroperoxide increased respiration, decreased membrane potential and mitochondrial matrix superoxide release rates of control but not UCP2- or iPLA2γ-silenced INS-1E cells. iPLA2γ/UCP2-mediated uncoupling was alternatively activated by an H2O2 burst, resulting from palmitic acid (PA) β-oxidation, and it was prevented by antioxidants or catalase overexpression. Exclusively, nascent FAs that cleaved off phospholipids by iPLA2γ were capable of activating UCP2, indicating that the previously reported direct redox UCP2 activation is actually indirect. Glucose-stimulated insulin release was not affected by UCP2 or iPLA2γ silencing, unless pro-oxidant activation had taken place. PA augmented insulin secretion via G-protein-coupled receptor 40 (GPR40), stimulated by iPLA2γ-cleaved FAs (absent after GPR40 silencing). INNOVATION AND CONCLUSION: The iPLA2γ/UCP2 synergy provides a feedback antioxidant mechanism preventing oxidative stress by physiological FA intake in pancreatic β-cells, regulating glucose-, FA-, and redox-stimulated insulin secretion. iPLA2γ is regulated by exogenous FA via β-oxidation causing H2O2 signaling, while FAs are cleaved off phospholipids, subsequently acting as amplifying messengers for GPR40. Hence, iPLA2γ acts in eminent physiological redox signaling, the impairment of which results in the lack of antilipotoxic defense and contributes to chronic lipotoxicity.
Keywords: Animals; Hydrogen Peroxide; Superoxides; Antioxidants; fosfolipasy A2, skupina II; oxidační stres; Cell Line, Tumor; Mitochondria; Membrane Potential, Mitochondrial; Uncoupling Protein 2; lipidy; sekrece inzulinu; terc-butylhydroperoxid; Oxidative Stress; receptory spřažené s G-proteiny; beta-buňky; peroxid vodíku; signální transdukce; mitochondriální proteiny; superoxidy; Insulin; Lipids; Signal Transduction; mitochondrie; Group II Phospholipases A2; iontové kanály; Ion Channels; Insulin Secretion; membránový potenciál mitochondrií; antioxidancia; Insulin-Secreting Cells; krysa rodu Rattus; Receptors, G-Protein-Coupled; uncoupling protein 2; Mitochondrial Proteins; zvířata; inzulin; tert-Butylhydroperoxide; Rats; nádorové buněčné linie